Influence of steam sterilization and raster angle on the deflection of 3D printing shapes: Rapid communication - Zaborniak, Małgorzata; Budzik, Grzegorz; Grzywacz-Danielewicz, Katarzyna; Józwik, Jerzy; Dziedzic, Krzysztof; Magniszewski, Marek; Rak, Danuta (Polimery, 2024)
The study examined influence of steam sterilization and the raster angle (0°, 90°) on the deflection of polymer shapes obtained by 3D printing. In the case of PEEK and PLA, the FDM/FFF method was used, in the case of photocurable resin, DLP technology, and in the case of MED610, PolyJet technology. It was shown that the raster angle, type of material and sterilization have a significant impact on the strength and deformation of the tested polymers. A model of a facial bone implant was also developed and the suitability of the tested materials for obtaining this type of implants was examined. The dimensional accuracy of the implant models was highest for the MED610 model. However, due to the significant deflection of this polymer under load, its use is only possible in areas of low stress. In the case of UV resin printed in the vertical direction (90°), the samples showed the least deflection and the printed model had no visible defects. The greatest deformations occurred at the ends and narrowing’s of the model.